2001
DOI: 10.1152/ajplung.2001.281.3.l660
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant proteins A and D in Eustachian tube epithelium

Abstract: collectin; innate immunity; in situ hybridization; immunoelectron microscopy THE EUSTACHIAN TUBE (ET) develops embryonically from the first pharyngeal pouch and connects the upper respiratory tract to the middle ear. The ET protects the middle ear from excessive fluctuations of atmospheric pressure, serves as a clearance tract, and may protect the middle ear against the invasion of microbes and other noxious agents from the airways (3). Infections in the middle ear are very common, affecting nearly all childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 42 publications
2
31
1
1
Order By: Relevance
“…One explanation could be the nature of induced sputum: generally these secretions are derived mainly from the large, more proximal airways and this leads to some problems in the reproducibility of these samples [23,24]. All sputum samples were included because SP-A is mainly expressed in epithelial cells, not only in the distal airways but also in trachea, sinus [46] and even middle ear epithelium [35,47]. The exact quantification of SP-A in the sputum supernatant is also somewhat problematic since sputum is not homogenous and both the induction and isolation process may vary between laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be the nature of induced sputum: generally these secretions are derived mainly from the large, more proximal airways and this leads to some problems in the reproducibility of these samples [23,24]. All sputum samples were included because SP-A is mainly expressed in epithelial cells, not only in the distal airways but also in trachea, sinus [46] and even middle ear epithelium [35,47]. The exact quantification of SP-A in the sputum supernatant is also somewhat problematic since sputum is not homogenous and both the induction and isolation process may vary between laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…SP-D (and MBL) is a member of the collectins, being produced by the alveolar type II cells and nonciliated bronchiolar cells and secreted into the alveolar lining layer, and was originally thought to have only surfactant function in the lungs (17). Interestingly, a recent study showed the presence of SP-D (and SP-A) in the epithelial cells of the porcine Eustachian tube (34), suggesting that they partake in the immune defence during middle ear infections. In view of the grossly increased risk of recurrent middle ear infections in TS patients, this finding could be of special importance.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few studies demonstrating surfactant in the upper airways, decreased levels of the various phospholipid components of surfactant have been implicated as playing a role in atrophic rhinitis [3] . Additionally, surfactant has been identifi ed in the porcine Eustachian tube and may contribute to lowering the opening pressure between the nasopharynx and middle ear [4][5][6] . Alterations in surfactant levels may adversely affect Eustachian tube function and contribute to chronic ear infections.…”
Section: Introductionmentioning
confidence: 99%